Palms used by Ashaninka indigenous people in Peruvian Amazon - Sosnowska, Joanna (2010)
In this paper we present traditional knowledge and importance of palms in Ashaninka people’s life. Qualitative and quantitative description is based on 32 interviews obtained during visits in seven native communities situ- ated near by Perene and Tambo rivers in Junín department of Peru. We registered 15 species of palms used by Ashaninka people; those were classified in five categories by use: food, construction, tools, ornaments and medicaments. Species with the most diverse uses were Attalea phalerata, Bactris gasipaes, Oenocarpus bataua and Socratea exorhiza. The most useful palm parts are fruits used mainly as a food. The proximity of Asháninkas communities from Perené Valley to the cities would produce a change in the traditional way of life, where palm trees are the most important natural resources used by them. However, the traditional life, knowledge and practice in using of palms are still alive in communities of Tambo River.